Evidence of Substantial Carbon Isotope Fractionation among Substrate, Inorganic Carbon, and Biomass during Aerobic Mineralization of 1,2-Dichloroethane by Xanthobacter autotrophicus - Hunkeler, Daniel; Aravena, R (My University, 2000)
Carbon isotope fractionation during aerobic mineralization of 1,2-dichloroethane (1,2-DCA) by Xanthobacter autotrophicus GJ10 was investigated. A strong enrichment of 13C in residual 1,2-DCA was observed, with a mean fractionation factor α ± standard deviation of 0.968 ± 0.0013 to 0.973 ± 0.0015. In addition, a large carbon isotope fractionation between biomass and inorganic carbon occurred. A mechanistic model that links the fractionation factor α to the rate constants of the first catabolic enzyme was developed. Based on the model, it was concluded that the strong enrichment of 13C in 1,2-DCA arises because the first irreversible step of the initial enzymatic transformation of 1,2-DCA consists of an SN2 nucleophilic substitution. SN2 reactions are accompanied by a large kinetic isotope effect. The substantial carbon isotope fractionation between biomass and inorganic carbon could be explained by the kinetic isotope effect associated with the initial 1,2-DCA transformation and by the metabolic pathway of 1,2-DCA degradation. Carbon isotope fractionation during 1,2-DCA mineralization leads to 1,2-DCA, inorganic carbon, and biomass with characteristic carbon isotope compositions, which may be used to trace the process in contaminated environments.